2022
DOI: 10.3389/fped.2022.777854
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Lactams Therapeutic Monitoring in Septic Children–What Target Are We Aiming for? A Scoping Review

Abstract: The antimicrobial therapy of sepsis and septic shock should be individualized based on pharmacokinetic/pharmacodynamic (PK/PD) parameters to deliver effective and timely treatment of life-threatening infections. We conducted a literature scoping review to identify therapeutic targets of beta-lactam antibiotics in septic pediatric patients and the strategies that have been applied to overcome sepsis-related altered pharmacokinetics and increase target attainment against susceptible pathogens. A systematic searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
(71 reference statements)
1
6
0
1
Order By: Relevance
“…In the intensive care unit, some authors recommend a target of free-C min /MIC ratio of up to 6. 8 Three of our successfully treated patients have C min /CMI below this target but maintained above 1, as suggested by some authors. The few dosages did not allow us to conclude whether lower targets could be generalized.…”
Section: Discussionsupporting
confidence: 77%
“…In the intensive care unit, some authors recommend a target of free-C min /MIC ratio of up to 6. 8 Three of our successfully treated patients have C min /CMI below this target but maintained above 1, as suggested by some authors. The few dosages did not allow us to conclude whether lower targets could be generalized.…”
Section: Discussionsupporting
confidence: 77%
“…18 Likewise, a recent scoping review concerning betalactams TDM among septic children showed that administration by prolonged or CI was implemented only in 2 studies, even if none of these investigated the probability of attainment of aggressive PK/ PD targets or the relationship with clinical outcome. 19 The aim of this study was to explore the relationship between PK/PD target attainment and microbiologic eradication in critically ill children with severe documented Gram-negative infections treated with CI beta-lactam monotherapy.…”
mentioning
confidence: 99%
“… 16 , 17 Only a few studies assessed the impact that prolonged or CI may have on PK/PD target attainment and clinical outcome among critically ill children treated with beta-lactams. 18 , 19 A cross-sectional survey on the implementation prolonged or CI of beta-lactams among neonatal sepsis patients found that only approximately 30% of respondents had access to this infusion modality. 18 Likewise, a recent scoping review concerning beta-lactams TDM among septic children showed that administration by prolonged or CI was implemented only in 2 studies, even if none of these investigated the probability of attainment of aggressive PK/PD targets or the relationship with clinical outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in critically ill adults, pharmacokinetic/pharmacodynamic targets between ƒt greater than MIC = 100% and ƒt greater than 4 × MIC = 100% are associated with better microbiological and clinical outcomes (5) and are commonly used for therapeutic drug monitoring (TDM) according to an international survey (6). However, optimal pharmacokinetic/pharmacodynamic targets still need to be better defined in children, and so far, pediatric studies have used conservative targets of ƒt greater than MIC between 40% and 50% up to aggressive targets of ƒt greater than 6 × MIC = 100% (7). Furthermore, it is unclear if identical pharmacokinetic/pharmacodynamic targets should apply to all septic children regardless of the infection source.…”
mentioning
confidence: 99%